ASUHAN KEPERAWATAN MEDIKAL BEDAH STROKE NON HEMORAGIK PADA NY. A DENGAN PEMBERIAN TERAPI GENGGAM BOLA KARET DENGAN MASALAH GANGGUAN MOBILITAS FISIK - Nia Oktavia; T. Eltrikanawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Non-hemorrhagic stroke is a central nervous system disease that clogs blood vessels, reduces oxygen supply to the brain, and disrupts the nervous system. The prevalence of non-hemorrhagic stroke patients at the Embung Fatimah Hospital in Batam City is 98 cases and is expected to continue to increase until 2025 (Denkes Batam City, 2023). This Professional Scientific Writing aims to carry out Medical Surgical Nursing Care on Mrs. A With The Provision Of Non-Pharmacological Therapy Holding Rubber Balls With Physical Mobility Disorders At The Embung Fatimah Hospital In Batam City In 2025. The method used in this Professional Scientific Paper is a case study carried out based on the stages of nursing care including review, diagnosis, intervention, implementation, and evaluation. The results of the Professional Scientific Writing were found complaints of difficulty in moving the upper and lower extremities with 2/2 muscle strength, increased blood pressure and skin damage due to bed rest with 3 nursing diagnoses, namely Physical mobility disorders related to neuromuscular disorders, Ineffective risk of cerebral perfusion associated with hypertension, and Skin/tissue integrity disorders related to decreased mobility. The intervention and implementation were carried out for 5 days and a nursing evaluation was obtained by Mrs. A that the activity starts to be done on its own, blood pressure improves, skin/tissue integrity improves. The strength value of the upper and lower extremity muscles increased to 4/3. Advice for Non Hemorrhagic Stroke sufferers to do Non Pharmacological Therapy Holding a Rubber Ball to be able to increase mobility and muscle strength values. Keywords: Nursing care, grip of rubber ball, non – hemorrhagic stroke.